Enhanced Oxygen Evolution Reaction Activity of Nanoporous SnO2/Fe2O3/IrO2 Thin Film Composite Electrodes with Ultralow Noble Metal Loading. Issue 3 (3rd December 2018) - Haschke, Sandra; Zhuo, Ying; Schlicht, Stefanie; Barr, Maïssa K. S.; Kloth, Ricarda; Dufond, Maxime E.; Santinacci, Lionel; Bachmann, Julien
Abstract: A conductive SnO2 layer and small quantities of IrO2 surface cocatalyst enhance the catalytic efficiency of nanoporous Fe2 O3 electrodes in the oxygen evolution reaction at neutral pH. Anodic alumina templates are therefore coated with thin layers of SnO2, Fe2 O3, and IrO2 by atomic layer deposition. In the first step, the Fe2 O3 electrode is modified with a conductive SnO2 layer and submitted to different postdeposition thermal treatments in order to maximize its catalytic performance. The combination of steady‐state electrolysis, electrochemical impedance spectroscopy, X‐ray crystallography, and X‐ray photoelectron spectroscopy demonstrates that catalytic turnover and e − extraction are most efficient if both layers are amorphous in nature. In the second step, small quantities of IrO2 with extremely low iridium loading of 7.5 µg cm −2 are coated on the electrode surface. These electrodes reveal favorable long‐term stability over at least 15 h and achieve maximized steady‐state current densities of 0.57 ± 0.05 mA cm −2 at η = 0.38 V and pH 7 (1.36 ± 0.10 mA cm −2 at η = 0.48 V) in dark conditions. This architecture enables charge carrier separation and reduces the photoelectrochemical water oxidation onset by 300 mV with respect to pure Fe2 O3 electrodes of identical geometry. Abstract : The combination of a conductive SnO2 layer and an IrO2 surface cocatalyst in one nanoporous Fe2 O3 electrode allows one to enhance the water oxidation activity at neutral pH. In this thin film composite electrode, charge carriers are efficiently separated in dark and bright conditions as opposed to the pure Fe2 O3 electrode.